Turismo e conservação no cenário rural do entorno de uma Unidade de Conservação, no município de Luiz Antonio (SP) - Severino, Fulvio Cesar Garcia (Universidade Federal de São Carlos, 2002)
The tourism in rural areas has stood out for allowing the conservation of natural areas that comprises the rural matrix and for having conditions to generate revenues and employments to the local population. In the present survey, six farms (located in surroundings of Jataí Ecological Station Luiz Antônio city/SP, Brazil) were visited with the aim to verify by interviews both its tour potential and the owners social representations concerning to land uses. In addition, it was intended to know postures, values and worries about the tour activities from the urban areas people to obtain a wiser view about tourism issue. The activities developed in farms compose the cast of touring possibilities in rural areas. Nevertheless the owners are not ready for tourism in their proprieties. Natural areas of their proprieties have been seen with dislike (negativist representation) due to impossibility of using them as incomes (utilitarian representation). The conservation unit has been seen as a biodiversity protection place (naturalist representation). However natural areas out of Ecological Station have not been comprehended as a place for conservation. Ecological Station was the most tour potential cited by interviewees in urban area. They also realize that the city still has not been ready for tourism due to a lacking infrastructure. Notwithstanding they believe tourism might be a generator of employments and revenues besides a social and economic factor of growth and development. Tourism is supposed to serve for this purpose without basing upon developmental myth referential as well as to be planned with and for population. For its formal implementation, there is the necessity of an incitement policy for tour activities based on environmental, social and economic diagnosis. There is also the necessity of sensitization efforts and environmental education with population. The main point is to train local guides consciousness from environmental, social and cultural queries and capable to spread its tour attributes away. It is important as well to choose a farm, to observe the evolution of tour activities and to monitory its results.
Keywords: Conservação; Turismo; Representação social; Rural tourism; Environment conservation; Social representation; CIENCIAS BIOLOGICAS::ECOLOGIA